KEPEMIMPINAN PEREMPUAN DALAM IBADAH: TAFSIR TRANSFORMATIF ATAS DISKURSUS IMAM PEREMPUAN BAGI LAKI-LAKI DALAM SHALAT - Munfarida, Elya (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2008)
Controversy about women ability as imam for men, have become polemic of past ulama. Four imam mazhab firmly refusewomen imamah to men. Ulama discourse about womenâ€™s imamah reflects their inclination to patriarchal interest. It is clear from theexistence of rational inconsistency on their thought: in one side on imam general prerequisite, religious understanding and al-Qurâ€™an fluentlyas main criteria. However, on the other side, when discussing about women imamah, those substantial criteria neglected. Their refusal didnot based on consideration whether women comply with qualification that being prerequisite, but simple because on â€œbecause she iswomanâ€. Meanwhile, Abu Tsaur, al-Thabari, and Mazini as ulama side whom absolute permit women as imam. However, their view did notemerge to surface; moreover almost disappear from Islamic thought discourse. On this point, the appointment of Ummu Waraqah as imamfor men can be understood as implementation and affirmation of human equality idea, which existed on tauhid doctrine. Therefore, men andwomen have chance to become imam, as long as comply with qualification prerequisite.